Analysis of Phatic Expression in Freedom Writer's Film - Asliana Tien; Yanto Yanto; Velmi Mayaputri (Leksikon: Jurnal Pendidikan Bahasa, Sastra, dan Budaya, 2023)
ABSTRACK Phatic expressions are rarely discussed in communication studies and are not known to many people even though the use of phatic expressions is often used in everyday life. The objective of research is to describe the types and functions of phatic expressions used in Freedom Writer’s film. The theory used Biber (in Aziz, 2015) and Kinneavy (in Chaer, 2009) to analysis the data of research. This research used descriptive qualitative research methods with observation and documentation data collection techniques. The results of this research found 11 types of phatic expressions contained in the characters' conversations in the Freedom Writer's film, namely: 1) interjection, 2) Greetings and Farewells, 3) Discourse markers, 4) Response, 5) Hesitators, 6) The politeness markers please, 7) Apologies, 8) Casual pronunciation, 9) Attention signal, 10) Thanks, 11) Expletives. Meanwhile, the functions of phatic expressions found in the film Freedom Writer’s include 4 functions: 1) Expression functions found in phatic expression types Thanks, Response, Expletive, Discourse markers, Interjection, and Apologies, 2) Information functions in the types of Discourse markers, Casual pronunciation and Responses, 3) Exploration function in the types of Response, Discourse markers and casual pronunciation types, 4) Persuasion function in Response types, Casual pronouncement and The politeness markers please.